Corrosion and Passivation Behaviour of Three Stainless Steels in Differents Chloride Concentrations - Lameche, Siham; Nedjar, Ratiba; Rebbah, Houria; Adjeb, Azzedine (Asian Journal of Chemistry, 2010)
The corrosion and passivation behaviour of three stainless steels were examinated in chloride-containing solutions using cyclic polarization techniques. The duplex stainless steels showed a pitting corrosion resistance higher than the conventional 13 % Cr and modified 13 % Cr stainless steels. The resistance of pitting of alloys depends on chemical composition such as molybdenum and nickel. The presence of sodium chloride enhanced metal electrodissolution at higher chloride concentrations. In addition to chromium and nickel, other alloying element like molybdenum, may be added to control structural balance and to improve corrosion resistance characteristics.